Kinetics of volatile aromatic compound production during the aging of cachaça in different types of wood - BRICENO, Julio Cesar Colivet; RABELO, Paula Novais; BELO, Lúcio; MENDES, Dianiny; CALIARI, Marcio; SILVA, Flavio; MORGADO, Cristiane; OLIVEIRA, Tatianne Ferreira de (Food Science and Technology, 2025)
This study evaluated cachaças aged up to 48 months in four types of wood (oak, amburana, balsam, and chestnut), with analyses performed every four months, totaling 48 samples per type of wood. Compounds such as ethyl acetate, ethyl lactate, and aldehydes were identified and quantified by gas chromatography and were kinetically modeled by the Peleg model. The results demonstrated that the model presented an excellent fit to the experimental data (R² > 0.94), indicating that the production of volatile compounds follows second-order kinetics. The initial production rate was higher in the first 24 months, with stabilization observed after this period. Tropical woods, like amburana, balsam, oak, and chestnut, presented a higher initial production rate than oak, demonstrating a slower but constant evolution throughout aging. Light and volatile compounds, such as acetaldehyde and ethyl acetate, predominated initially, contributing to fresh and fruity aromatic profiles. Compounds with a higher molecular weight, as ethyl palmitate and phenols, became more evident in the final stages and were associated with denser and more complex sensory notes. This study highlights the significant impact of wood type and aging time on the chemical and sensory profile of cachaça, providing valuable information for optimizing the aging process and developing beverages with unique aromatic characteristics.